Septic Arthritis of the Pediatric Shoulder: From Infancy to Adolescence - Justin W. Walker; William L. Hennrikus (International Journal of Pediatrics)
Background. Septic arthritis of the glenohumeral joint in the pediatric population (<18 yo) is not commonly described in the literature. There is a corresponding paucity of information regarding its presentation and treatment. Methods. An IRB approved review of patients treated with irrigation and debridement by the Orthopaedic Department was completed. This retrospective study includes four patients, presenting from 2005 to 2015, with septic arthritis of the shoulder. Results. The mean age (Mage) at presentation was 5 years, with a range of 1 month to 15 years. Patients presented on average after 7 days with pain and a mean temperature of 39°C, erythrocyte sedimentation rate of 66 mm/hr, a C-reactive protein level of 11.17 g/dL, and a white blood cell count of 20.2 × 103/mcL. Staphylococcus aureus, Candida albicans, and Pseudomonas aeruginosa were cultured from the wounds. All cases were treated operatively with irrigation and debridement and with antimicrobial therapy. Patients received antibiotics for an average of 6 weeks. Conclusion. Septic arthritis of the shoulder occurs in all pediatric ages. Successful treatment of septic arthritis of the shoulder was accomplished in four cases without division of the biceps sheath, with an average follow-up of 8 months.